THE DETERMINANTS OF ASSETS GROWTH OF SHARIA LIFE INSURANCE COMPANIES IN INDONESIA FOR THE 2013-2018 PERIOD - Sulistio Purwaningrum; Dian Filianti (Universitas Airlangga, 2020)
This study aims to examine and determine the determinants of asset growth in Sharia Life Insurance Companies in the 2013-2018 period. This study uses a quantitative approach with the data used are secondary data from the financial statement panel data of each Sharia Life insurance company. The independent variables used in this study are Participant Contributions, Investment Returns, Operating Expenses, and Claims. The dependent variable is the growth of Sharia Life Insurance Company Assets in Indonesia for the period 2013-2018. The population in this study amounted to 30 Sharia life insurance companies registered with the Financial Services Authority. The sampling technique in this study was purposive sampling with 11 companies selected as samples. . The results of this study indicate that partially the participant contributions and claims variables have a significant negative effect. Investment returns and operating expenses have a significant positive effect on the growth of sharia life insurance company assets. Simultaneously participant contributions variables, investment returns, operating expenses, and claims show a significant influence on the growth of sharia life insurance company assets. Keywords: Participant Contributions, investment returns, operating expenses, claims, asset growthREFFERENCE Ahmed Salman Syed, Hafiz Majdi Ab. Rashid, Sheila Nu Nu Htay. The impact of internal forces on acceptance oftakaful by insurance policy-holders in India. Journal of IslamicAccounting and Business Research, 9(5), 673-686.Ainul, F. N. A., Susyanti, J., & Mardani, R. M. (2017). Pengaruh premi, klaim, hasil underwriting, investasi dan profitabilitas terhadap pertumbuhan aset pada perusahaan asuransi jiwa syariah di Indonesia. Jurnal Ilmiah Riset Manajemen, 6(2), 97-110.Ajija, S. R., Sari, D. W., Setianto, R. H., & Primanti, M. R. (2011). Cara cerdas menguasai Eviews. Jakarta: Salemba Empat.Ali M. Mahbubi, Rusni Hassan, Shabana M. Hasan. (2014). An exploratory study of shari'ah issues in the application of tabarru' for takaful. Global Review of Islamic Economics and Business, 1(3), 164-174.Al-Qur'an dan terjemahan. Kementrian Agama Republik Indonesia. 2018Fatwa Dewan Syariah Nasional No 21/DSN-MUI/X/2001 Tentang Pedoman Umum Asuransi SyariahGhofar, A. (2012). Pengaruh premi, klaim, investasi dan profitabilitas terhadap pertumbuhan aset pada perusahaan asuransi syariah di Indonesia. Skripsi tidak diterbitkan. Yogyakarta: Fakultas Syari’ah Dan Hukum Universitas Islam Negeri Sunan Kalijaga.Inderastuti, A., Budi, S., & SEI, M. S. I. (2018). Pengaruh klaim, hasil underwriting, dan biaya operasional terhadap pertumbuhan aset perusahaan asuransi jiwa syariah di indonesia periode 2012-2016. Skripsi tidak diterbitkan. Surakarta: Institut Agama Islam Negeri Surakarta.Melia, R., & Muharram, R. S. (2018). Pengaruh premi, investasi, dan beban klaim terhadap pertumbuhan aset perusahaan asuransi jiwa syariah di indonesia periode 2012-2016. Skripsi tidak diterbitkan. Surakarta: Institut Agama Islam Negeri Surakarta.Muhammad Syakir Sula. (2004). Asuransi syariah: (life and general) konsep dan sistem operasional. Jakarta: Gema Insani.Murniati Mukhlisin. (2017). Unveiling IASB standardization projects and its influence on the position of Takaful industry in Indonesia. Journal of Islamic Accounting and Business Research, 8(2), 229-247Otoritas Jasa Keuangan (2014). Statistik Perasuransian Indonesia Tahun 2013_______. (2015). Statistik perasuransian Indonesia Tahun 2014_______. (2016). Statistik perasuransian Indonesia Tahun 2015_______. (2017). Statistik perasuransian Indonesia Tahun 2016_______. (2018). Statistik perasuransian Indonesia Tahun 2017_______. (2019). Statistik perasuransian Indonesia Tahun 2018PT. AIA Financial. Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.aia-financial.co.idPT. Allianz Life Indonesia. Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.allianz.co.idPT. Asuransi Jiwa Syariah Al Amin. Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.alamin-isurance.comPT. Asuransi Jiwa Syariah Amanahjiwa Giri Artha. Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.amanahgitha.comPT. Axa Financial Indonesia. Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.axa.co.idPT. Great Eastrn Life Indonesia. Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.greateasternlife.comPT. Jiwa Central Asia Raya. Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.car.co.idPT. Jiwa Manulife. Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.manulife-indonesia.comPT. Panin Daichi Life . Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.panindai-ichilife.co.idPT. Prudential Life Assurance . Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.prudential.co.idPT. Tokio Marine Life Insurance. Laporan Keuangan (Online). di unduh 3 Januari 2020, dari http://www.tokiomarine.comPeraturan Menteri Keuangan Nomor 18/PMK.010/2010 Tentang Penerapan Prinsip Dasar Penyelenggaraan Usaha Asuransi dan Usaha Reasuransi dengan Prinsip Syaraih._______. Nomor 11/PMK.010/2011 Tentang Kesehatan Keuangan Usaha Asuransi dan Usaha Reasuransi dengan Prinsip SyariahSoemitra, A. (2009). Bank & lembaga keuangan Islam. Jurnal Islamika, 15(1), 89-112. https://doi.org/10.1007/BF0141590